Academic Service Quality Of Student Loyalty With Student Satisfaction As Intervening Variables In PTS X - Novianto Eko Nugroho (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
The quality of academic services is to refer to academic services provided by education institutions / institutions to students as stakeholders. The quality of best academic services is based on the performance of variety groups of educators, education staff and more over janitors. The purpose of this study was to determine the effect of service quality directly influence student satisfaction and to find out the effect of service quality indirectly affected student loyalty through student satisfaction. This research method uses quantitative methods with explanatory research types. The subjects of this study were S1 "X" S1 and D3 study program students in Surabaya, which in total 98 active students. To test the effect of intervening variables, the path analysis method is used. Path analysis is a direct development of multiple regression forms with the aim of estimating the magnitude and significance (significance) of hypothetical causal relationships in a set of variables. The results showed that the existence of a positive and significant effect simultaneously between service quality variables on student loyalties, while service quality variables through student satisfaction indirectly affect student loyalty.